The Influence of Magnetic Field on the Enrichment by Polymeric Membranes - Grzywna, Z. J.; Rybak, A.; Borys, P.; Pawelek, K. (Journal of Applied Membrane Science & Technology, 2017)
An idea of using magnetic field to enhance oxygen transport, as an effective factor for the air enrichment, has already been successfully demonstrated. Direct consequence of this concept was to produce polymeric magnetic membranes by casting technique. An analysis of experimental data, obtained from transient and stationary states of mass transport, allowed to formulate a hypothesis of a â€œdead thicknessâ€ of magnetic membranes in question, i.e. the bulk polymer phase as a part of membrane with no magnetic channels but limiting the overall transport through it. It will be shown that removing this part increases the rate of transport and enhances the air separation. To complete the overall approach, the theory is provided both on phenomenological and molecular levels. The simulation by Monte Carlo and Brownian dynamics, to show some molecular properties of magnetic field and its activity during separation, was performed.